AN ANALYSIS OF SUBTITLING STRATEGY ON NETFLIX DOCUMENTARY FILMS “OUR PLANET” - I Gusti Agung Ayu Sasmitha Dewi Anggita Pramestya; Baharuddin; Lalu Jaswadi Putera; Lalu Ali Wardana (STKIP Subang, 2024)
The development of AVT has a close connection with technology and the entertainment industry, one of which is film. Films interest all over the world, so subtitling was needed in subtitling countries. The research was aimed to discover: 1) what subtitling strategies of Gottlieb are used by the translator; (2) what is the most frequently used subtitling strategies of Gottlieb used by the translator. This research used a descriptive qualitative method to identify and describe the subtitling strategies of Gottlieb on Netflix Documentary Films and the most frequently used subtitling strategies. The data was analyzed using Gottlieb subtitling theory (1992). The results of the research showed that seven subtitling strategies are used in all eight-film series of Netflix Documentary Films: transfer, expansion, condensation, imitation, paraphrase, transcription, & deletion. The most frequently used subtitling strategies in this research are transfer strategy with 71.11%, imitation with 5.03%, and expansion with 8.31% of the total data collected.